Building Powerful Learning Environments : From Schools to Communities. - Bokas, Arina (Rowman & Littlefield Publishers, 2016)
Building Powerful Learning Environments takes a close look at the trends of the Post-Digital Era through the prism of how systems of education can meet the needs of our times and offers a systemic approach to creating a different canvas for learning that aligns to these changes. At the center of the book are the concepts of a learning environment and a culture of partnerships.